A rare case of hidebound disease with dental implications - Vikram Bali; Sarita Dabra; Ashima Bali Behl; Rajiv Bali (Wolters Kluwer Medknow Publications, 2013)
Systemic sclerosis (also called as Scleroderma or hidebound disease) is a chronic sclerotic disease of unknown etiology which causes diffuse, increased deposition of extra cellular matrix in connective tissue with vascular abnormalities, resulting in tissue hypoxia. The disease is characterized by diffuse fibrosis; degenerative changes; and vascular abnormalities in the skin (scleroderma), articular structures, and internal organs. Aesthetic and facial dysfunctions are followed by important oral and facial manifestations. Most oral manifestations begin with tongue rigidity and facial skin changes. Bone resorption of mandibular angle and widening of periodontal ligament space on periapical radiographs are important radiological findings. Other systemic changes include the involvement of internal organs, which lead to serious complications as well as disorders in the cardiac muscle and Raynaud΄s phenomenon. This is a case report of 30-year-old female patient with the classical features of this disease. This case is reported for its rarity and variable expressivity. The main aim of this article is to describe thorough presentation of the case report, various forms of scleroderma, pathogenesis, oral, extraoral, periodontal manifestations of scleroderma, and its treatment options. A brief review of the literature, focusing on dental alterations is also presented.